Determinants of Bitcoin Returns: An Analysis of Bitcoin Information, Macroeconomics, and Other Cryptocurrency Markets - Sihombing, Septiana; Sahputri, Rindi Ardika Melsalasa; Ali, Hendrik; Njoman, Muhamad Galy; Lumbantoruan, Ronaldo Fransiskus; Syafitri, Ezzy (Jurnal Ilmu Keuangan dan Perbankan (JIKA), 2025)
The bitcoin market has exhibited highly volatile return movements, experiencing a sharp surge starting from in November 2022 to 2024. This significant fluctuation underscores the importance of analyzing the factors influencing bitcoin’s return dynamics. This study utilizes daily data with a final sample of 590 observations. All time-series variables must be stationary before being processed in the statistical model. The analysis was conducted using Stata 16 software. To ensure the absence of unit roots, the stationarity of the research variables was tested using the Augmented Dickey-Fuller (ADF) and Phillips-Perron (PP) tests. The findings indicate that market capitalization, gold, and litecoin have no significant impact on bitcoin returns. In contrast, miners’ revenue has a significant negative effect, while hashrate, mining difficulty, and the S&P 500 exhibit a significant positive influence on bitcoin returns. This study highlights bitcoin’s role as a store of value and investment asset, emphasizing the impact of hashrate and mining difficulty on its returns and integration into financial markets, particularly the S&P 500. The findings provide insights for investors on portfolio diversification and assets like a gold and equities. Additionally, the study underscores the importance of sustainable mining practices and regulatory policies to balance cryptocurrency’s economic potential with environmental sustainability. Keywords: Market capitalization; Mines’s Revenue; Hashrate; Mining difficulty; Commodity Asset, Cryptocurrency